2002
DOI: 10.1006/viro.2002.1554
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Reverse Transcription Is Stimulated by Tat from Other Lentiviruses

Abstract: The tat gene is required by HIV-1 for efficient reverse transcription and this function of Tat can be distinguished from its role in transcription by RNA polymerase II using tat point mutations that abrogate each function independently. The mechanism of Tat's role in reverse transcription, however, is not known, nor is it known whether this role is conserved among trans-activating factors in other retroviruses. Here we examine the abilities of heterologous viral trans-activating proteins from jembrana disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Finally, this study confirms previous reports that Tat Y47 was essential for virus replication in H9 cells and further showed that a Y47D mutation in Tat imparted a significant reverse transcription defect that, in conjunction with a small gene expression defect, impeded virus replication (12,26). Our data indicate that the reduced viral fitness observed by Verhoef et al (26) was likely due to combined inefficiencies in transcription and reverse transcription.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Finally, this study confirms previous reports that Tat Y47 was essential for virus replication in H9 cells and further showed that a Y47D mutation in Tat imparted a significant reverse transcription defect that, in conjunction with a small gene expression defect, impeded virus replication (12,26). Our data indicate that the reduced viral fitness observed by Verhoef et al (26) was likely due to combined inefficiencies in transcription and reverse transcription.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that HIV-1 Tat improved the efficiency of minus-strand SS DNA synthesis using a transcomplementation system (9,12,22). Briefly, we made a 293 cell line stably transfected with HIV-1 with a functional deletion of the tat gene, called 293HIV⌬tat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems unlikely that this second Tat function involves binding to TAR RNA, since the Tat-TAR binding study demonstrated that the mutations in the SIV-rtTA TAR element prevent Tat binding. Multiple additional roles for Tat have been suggested in HIV-1 biology; for example, Tat has been reported to affect mRNA capping, splicing, and translation (14,18,20,21,23,67,69,78), to stimulate reverse transcription (1,36,37,42,43,71), and to suppress RNA interference (7,35). Moreover, Huang et al demonstrated that HIV-1 variants regulated by the Gal4-VP16 transactivator protein require Tat for infectivity (38), and we recently observed that the introduction of a frameshift mutation in the HIV-1 Tat gene, which prevents Tat production, abolished HIV-rtTA replication.…”
Section: Discussionmentioning
confidence: 99%